OPTIMALISASI KEPATUHAN WAJIB PAJAK PBB MELALUI TEMPAT PEMBAYARAN MOBIL KELILING DAN PETUGAS KELURAHAN DI BPPKAD KOTA KEDIRI (AKSIME : Jurnal Pengabdian Masyarakat Bidang Akuntansi, Manajemen & Ekonomi, 2024)
The increase in land and building tax (PBB)-P2 payments in Kediri City through mobile services and village officials is an interesting phenomenon. and urban village officers is an interesting phenomenon. From the available data, payment through urban village officers is more widely used by the community than the mobile car. mobile car. This community service activity combines learning and community service. The goal is to make it easier for people to pay taxes, provide education, and increase the role of village officers. Results and discussion results and discussion show that both technological approaches and direct services to the community are equally important for improving tax compliance. Providing wider access to payment can optimize taxpayer compliance. Keywords: Compliance, Taxpayer, Land and Building Tax, Mobile Car, Village Officer